The liquid-hydrogen absorber for MICE - Bayliss,V; Boehm,J; Bradshaw,T; Courthold,M; Harrison,S; Hills,M; Hodgson,P; Ishimoto,S; Kurup,A; Lau,W; Long,K; Macwaters,C; et al. (IOP Publishing, 2019)
This paper describes the liquid hydrogen system constructed for The Muon Ionization Cooling Experiment (MICE); MICE was built at the STFC Rutherford Appleton Laboratory to demonstrate the principle of muon beam phase-space reduction via ionization cooling. Muon beam cooling will be required at a future proton-derived neutrino factory or muon collider. Ionization cooling is achieved by passing the beam through an energy-absorbing material, such as liquid hydrogen, and then re-accelerating the beam using RF cavities. This paper describes the system creating the 22l of liquid hydrogen within the MICE beamline; the necessary safety engineering, the liquid hydrogen absorber and its associated cryogenic and gas systems are presented, along with its performance.